Blood serum immunoglobulins of patients with multiple myeloma are capable of hydrolysing histone H1 - Magorivska, I.; Bilyy, R.; Shalay, O.; Loginsky, V.; Kit, Y.; Stoika, R. (Experimental Oncology, 2009)
Background: Recently we have shown that the imunoglobulins G from blood serum of some multiple sclerosis patients are capable
of cleaving histone H1. Aim: To check whether histone H1-hydrolyzing abzymes could be detected not only in blood plasma of autoimmune
patients, but also during cancer development, particularly during the onset of multiple myeloma. Methods: Immunoglobulines
were isolated from blood serum of multiple myeloma patients (n = 11) by precipitation with 50% ammonium sulfate and tested for
proteolytic activity toward linker and core calf thymus histones. Antibody preparations able to cleaved histone H1 were subjected
to affinity chromatography on histone H1-Sepharose with following analysis of chromatographic fractions’ protease activity. To
prove that antibody molecules are responsible for hydrolysis of histone H1, gel filtration at acidic pH with subsequent examination
of protease activity of chromatographic fractions (pH-shock analysis) was used. Results: It was found that 3 of 11 antibody
preparations are capable of hydrolyzing calf thymus histone H1 but not core histones. It was shown that histone H1-hydrolysing
activity of 2 proteolytically active antibody preparations is associated with IgGs that possess affinity towards histone H1. pH-shock
analysis proved that protease activity towards histone H1 is intrinsic property of IgG molecules. Conclusions: We demonstrated the
existence of previously unknown histone H1 hydrolyzing IgG abzymes in the serum of multiple myeloma patients. Possible biological
role of hisH1-hydrolyzing antibodies in patients with multiple myeloma was discussed.